Papers supported by the All Cypriniformes Species Inventory Project (ACSII) including those presented at the International Conference inChiang Mai, Thailand, 13–16 January 2012 (COVER) - Page, Lawrence M.; Mayden, Richard L.; Pethiyagoda, Rohan; Armbruster, Jonathan W. (Zootaxa, 2012)
(COVER)